Small renal pelvis stones: Shock wave lithotripsy or flexible ureteroscopy? A match-pair analysis - Gürbüz, Zafer Gökhan (Turk J Urol, 2019)
OBJECTIVE: Kidney stones in renal pelvis may be treated using various methods. For larger stones, percutaneous nephrolitotomy (PNL) is the first choice of option; where for smaller stones, shock wave lithotripsy (SWL) or flexible ureteroscopy (F-URS) could be more suitable options. In this article we aimed to compare the outcomes of F-URS and SWL on the treatment of renal pelvis stones <10 mm. MATERIAL AND METHODS: Files of patients treated with SWL and F-URS for renal pelvis stones <10 mm between March 2013 and May 2016 in our clinic were analyzed. For comparison, a match-pair analysis was designed. Complete stone removal was considered success. RESULTS: Forty patients were treated using F-URS (Group 1) and 40 patients underwent SWL (Group 2). Patients were assessed the day after the last session of the procedure. The early stone-free rates were 70% (28/40) in Group 1, and 15% in Group 2 (p<0.05). The same analysis was performed after three months. Stone-free rates were 100% and 92.5% in Groups 1 and 2, respectively (p=0.079). Three patients in Group 2 were not stone free after 3 sessions of SWL and considered unsuccessful. They were all successfully treated by F-URS. CONCLUSION: Even though there is no statistical difference among groups, our data may be interpreted as having better outcomes and tolerability with F-URS than SWL. We believe F-URS may have a great treatment prospect in this particular patient group.